2023
DOI: 10.3389/fnut.2023.1162934
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of fucoidan on TNF-α-induced inflammation in human retinal pigment epithelium cells

Abstract: Sargassum horneri (S. horneri) is a brown seaweed that contains a fucose-rich sulfated polysaccharide called fucoidan and is known to possess beneficial bioactivities, such as anti-inflammatory, antiviral, antioxidative, and antitumoral effects. This study aimed to determine the anti-inflammatory effects of AB_SH (hydrothermal extracts from S. horneri) and its bioactive compound (fucoidan) against tumor necrosis factor alpha (TNF-α)-induced inflammation in human retinal pigment epithelial (RPE) cells. AB_SH di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Additionally, in our previous study, we confirmed that fucoidan has an anti-inflammatory effect against inflammation induced by TNF-α in ARPE-19 cells. Compared to these results, loliolide reduced chemokine secretion more than fucoidan [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, in our previous study, we confirmed that fucoidan has an anti-inflammatory effect against inflammation induced by TNF-α in ARPE-19 cells. Compared to these results, loliolide reduced chemokine secretion more than fucoidan [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…ARPE-19 cells were seeded into 12-well plates at a density of 1 × 10 5 cells/well and incubated for 24 h. After incubation, uf-UPs (0.1, 1, and 10 µg/mL) or loliolide (25,50,100,200, and 400 µM) was added at the indicated concentrations, and cells were further incubated for 24 h at 37 • C in humidified air with 5% CO 2 . The concentration of S. horneri was determined based on previous studies [14]. A stock solution of MTT (5 mg/mL in PBS) was added to each well at a final concentration of 0.5 mg/mL according to the manufacturer's protocol.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Tibetan burnip polysaccharide reduces the expression of ICAM-1, VCAM-1, IL-6, IL-1β, and TNF-α partially by downregulating PPARγ in hyperlipidemic rats ( 203 ). Moreover, intake of low dose sucrose (7.5 mg/ml) is found to activate PPARγ via restoring microbial dysfunction and upregulating SCFAs levels, thereby suppressing MAPK/NF-κB signaling pathway, while high dose sucrose (30 mg/ml) exacerbates DSS-induced colitis ( 204 ). Additionally, Astragalus polysaccharide inhibits protein kinase A/p38 MAPK signaling pathway and the expression of PPARγ and PGC-1α, suppressing inflammation in heart failure rats ( 190 ).…”
Section: Natural Compounds In Regulation Of Pparsmentioning
confidence: 99%